Prioritizing economic growth : enhancing macroeconomic policy choice - Bradford, Colin I. (UN New YorkUS, 2005)
Attempts to lay out a logic for the notion that macroeconomic policy can indeed play a role in stimulating economic growth and employment, despite the many realistic constraints on its conduct.